Eficiência da manipueira como quelatizante de zinco e seu efeito na nutrição mineral do feijoeiro (Phaseolus vulgaris L.) - Melo, Vítor e Silva (2010)
Cassava (Manihot esculenta, Crantz) is considered a vital agricultural crop due to its role as a staple food for low-income populations, primarily in the North and Northeast of Brazil, and is used as raw material for the manufacturing of a number of products such as flour and starch. During the manufacturing of these products, a potentially toxic liquid residue called manipueira is produced. Due to its high content of hydrogen cyanide (HCN), this residue (which originates during the initial processing stages of the cassava) has very limited use. After undergoing a process of HCN volatilization however, it may then be used for the fertilization, to create insecticides, nematicides and herbicides. Manipueira has contains glucose, cyanogenic glycosides, organic substances and mineral nutrients, in particular potassium (K), nitrogen (N), as well as micronutrients - all guaranteeing its potential as a fertilizer. The aim of this study was to evaluate the effect of cassava as an alternative to zinc chelates in bean cultivation. The study was carried out in a greenhouse at the Federal University of Sergipe. The experimental design involved random blocks in 5x4 factorial arrangement, with five repetitions and five treatment sources: The experimental design was randomized blocks in a factorial arrangement 5 x 4, the treatments were five sources (A-H2O; Manipueira1 B-2 ml dm-3, C-4 manipueira2 ml dm-3, D-manipueira3 8mL dm3, E-EDTA) with four levels of zinc (0,0; 1,3;2,6 and 5,2 mg Zn dm3), applied to the soil, whit four replication. The soil was collected from the rural campus at the Federal University of Sergipe and a sample was taken for chemical analysis. The soil was placed in 16 L-1 b plastic bags and dolomitic lime was used for liming of the soil. The fertilizations were performed with 100 mg of phosphorus (P) dm-3 and 100mg of potassium (K) dm-3, in the form of triple super phosphate and potassium chloride. The lime and fertilizers were combined with the soil contained in the plastic bags and were then transferred to 100 containers with a soil capacity of 13 dm-3. A quantity of 50 mg of N dm-3 in the form of urea was applied for sowing fertilization. Sowing was carried out using six Pearl bean cultivar seeds per container. Seven days after the emergence of shoots, thinning was carried out to remove plant surplus, leaving two plants per container, and the treatments were applied. Once most of the plants had reached the phenological stage of flowering (R6) harvesting was carried out. The parameters examined were physico-chemical analysis (in the manipueira) and growth and nutritional analyses in the bean plant tissue (leaf and root). The use of cassava as quelatizante of micronutrients on dry bean crop had a satisfactory result in treatments EDTA and Man ¹.If necessary more studies of manipueira as chelate micronutrients in other cultures.